Macro-organization of photosynthetic complexes during salt stress acclimation of green microalgae and in plant chloroplast acetyltransferase and Ser/Thr protein kinase mutants - Kanna Sai Divya (2022)
During my doctoral work, my aim was to study the changes that occurred as a result of salt stress i) in the structure and function of the photosynthetic apparatus of Chlamydomonas reinhardtii (C. reinhardtii) ii) in the acclimatization reactions of Euglena gracilis (E. gracilis), and iii) to explore the role of protein acetylation/phosphorylation in Arabidopsis thaliana (A. thaliana) in the membrane dynamics of the photosynthetic apparatus. Salt stress had a negative effect on the growth and chlorophyll content of E. gracilis cells, as well as on the macro-organization of thylakoid membranes (TM), but had no effect on photosynthetic processes and the composition of photosynthetic complexes. At the same time, the carotenoid-chlorophyll ratio and the biotechnologically significant paramylon content increased. Accumulation of storage polysaccharide, changes in pigment composition and TM organization can help in the acclimation of E. gracilis cells to salt stress. We investigated the effect of salt stress on C. reinhardtii wild type and two stt7 and pgrl1 mutant strains. We showed that salt stress affected the repeat distance of TM; on the organization and functioning of pigment-protein complexes. The increased sensitivity of the stt7 mutant to salt stress suggests that photosynthetic state transitions play a key role in acclimation to salt stress. We investigated the role of chloroplast acetyltransferase (GNAT2) and STN7 kinase in the organization of A. thaliana TM. CD spectroscopic studies showed differences in the structure and arrangement of the PSII-LHCII supercomplex and/or LHCII in both gnat2 and stn7 mutants compared to the wild type. These results confirmed that GNAT2, like the STN7 kinase, is involved in shaping TM macroorganization. In general, it can be said that the dynamic organization of the membrane plays a key role in the stress adaptation of photosynthetic organisms, in which the post-translational modification of proteins may also play a role.